Climate Change and Community Resilience 2021
DOI: 10.1007/978-981-16-0680-9_4
|View full text |Cite
|
Sign up to set email alerts
|

What Motivates Farm-Level Adaptation in India? A Systematic Review

Abstract: Indian farmers are adopting several farm-level adaptation options to mitigate potential impacts from climate changeand extreme events. Although different studies have identified determinants, there is limited literature on systematic review of factors that drive farmer’s adaptive behaviour, particularly in India. This chapter aims to address this gap, and in doing so, it furnishes three major findings. First, non-climatic factors like demographic characteristics, asset and income, education, dependency on agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 44 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…[1]). Although agricultural growth is impossible without mechanization, low adoption has been reported in India [1,[11][12][13]. Numerous studies, therefore, identified the confounding factors of adoption, and those are related to economics, farm organization, demographics, extension agents, risk aversion behavior, social learning, and environmental conditions [11,12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1]). Although agricultural growth is impossible without mechanization, low adoption has been reported in India [1,[11][12][13]. Numerous studies, therefore, identified the confounding factors of adoption, and those are related to economics, farm organization, demographics, extension agents, risk aversion behavior, social learning, and environmental conditions [11,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although agricultural growth is impossible without mechanization, low adoption has been reported in India [1,[11][12][13]. Numerous studies, therefore, identified the confounding factors of adoption, and those are related to economics, farm organization, demographics, extension agents, risk aversion behavior, social learning, and environmental conditions [11,12,14]. On the other hand, several impact evaluation studies have estimated the impact of these technologies on reducing poverty and enhancing yield across African and Asian countries [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are a growing number of studies with reference to two aspects: identifying determinants and evaluating effectiveness across geographical locations as well as disasters. In regard to the former, studies identify the major influential factors under socioeconomic characteristics, farm characteristics, agro-climatic and meteorological conditions, and risk attitude behavior of the households (see Bahinipati & Patnaik, 2021). Several studies, on the other hand, also look into the extent of loss and damage (L&D) or impact that could be mitigated by enhancing resilience capacity of society through various generic and disaster-specific adaptation measures (Bahinipati & Patnaik, 2015, 2020Patnaik et al, 2017Patnaik et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%